Therapeutic pathomorphosis in malignant glioma tissues after photodynamic therapy with сhlorin e6 (reports of two clinical cases) - A. Yu. Rynda; D. M. Rostovtsev; V. E. Olyushin; Yu. M. Zabrodskaya (Biomedical Photonics)
In recent years, photodynamic therapy (PDT) has been increasingly introduced into the surgical practice of treating malignant neoplasms. In this publication, the authors show the appearance of therapeutic pathomorphosis in vivo in human malignant glioma cells after intraoperative photodynamic therapy. Tissue samples obtained 10–14 days after PDT revealed nuclear and cytoplasmic signs indicating apoptosis, necrosis, and autophagy. A decrease in the proliferative activity of glial tumor cells and their higher death count were detected.. Immunohistochemical analysis shows decreases expression of Ki-67 cell proliferation marker and decreased amount of transcription factor protein p53.